Penyelesaian Sengketa Perbatasan Antara Thailand Dan Kamboja Melalui Mekanisme Asean - Elfia Farida (Faculty of Law, Universitas Diponegoro, 2014)
A dispute between Thailand and Cambodia border fighting over an area of ??4.6 square kilometers around the Preah Vihear temple resolved through ASEAN mechanism. This study aims to describe, explain and analyze the ways and the efforts made ??by ASEAN. The research method used is juridical- normative. Data were analyzed qualitatively. The ways of dispute settlement that can be done is by peaceful means through dialogue, consultation, negotiation, good offices, conciliation and mediation by agreement of the parties to the dispute in accordance with the TAC. ASEAN is the effort made diplomatic efforts to avoid violence. A